James G. Carrier (comp.). History and Tradition in Melanesian Anthropology. Berkeley; Los Ángeles; Oxford: University of California Press, 1992. 257 pp. - Devalle, Susana B. C.; Carrier, James G. (El Colegio de México, 1998)
-